Solasonine Inhibits Pancreatic Cancer Progression With Involvement of Ferroptosis Induction - Liang, Xiaoqiang; Hu, Cheng; Han, Mian; Liu, Congying; Sun, Xun; Yu, Kui; Gu, Honggang; Zhang, Jingzhe (Frontiers in Oncology, 2022)
Pancreatic cancer is a highly fatal malignant tumor of the digestive system. It is characterized by early metastasis and high mortality rates. Solasonine, a steroidal alkaloid, is derived from Solanum nigrum L., a natural herb. Solasonine is associated with excellent anti-tumor effects, however, its effects on pancreatic cancer have not been fully established. Pancreatic cancer cells (PANC-1 and CFPAC-1) were used to verify the in vitro and in vivo effects of solasonine. Metabolomics were used to evaluate its underlying mechanisms. Solasonine promoted PANC-1 and CFPAC-1 cell apoptosis while inhibiting their proliferation, migration and invasion. Mouse xenograft models and metastasis models of ANC-1 and CFPAC-1 confirmed that solasonine blocked tumor formation and metastasis. Metabolomics confirmed the effects of solasonine on glutathione metabolism and SLC7A11-mediated ferroptosis. Furthermore, Co-Immunoprecipitation and Duolink® in situ PLA confirmed that OTUB1, a deubiquitylating enzyme, interacted with SLC7A11 and solasonine to enhance ubiquitinated degradation of SLC7A11 in PANC-1 and CFPAC-1 cells. Besides, molecular docking confirmed that solasonine directly bound TFAP2A and suppressed its protein levels. Bioinformatics and luciferase assays revealed that TFAP2A binds the OTUB1 promoter region, thereby promoting its transcription. In summary, solasonine inhibits the TFAP2A/OTUB1 SLC7A11 axis to activate ferroptosis and suppress pancreatic cancer cell progression.